What's in a Name? Effect of Alphabetical Ordering on Students' Achievement Example from Czech Elementary and Lower Secondary Schools - Regéczy, Martin (2011)
Humans are born with innate abilities that vary across individuals. Those innate abilities are at their origin unaffected by their name. Yet, as a child grows up it can be put in different situations based solely on name it holds. Those situations alter individuals' behavior in allocation of scarce resources (Carlson and Conrad, 2008) and consequently its earnings (Jurajda and Munich, 2007). At origin of these empirically observed differences might be use of alphabetical ordered lists at elementary and lower secondary schools. The empirical test I conducted fails to reject the null hypothesis that there is relation between surname initials and student achievement. Those at the bottom of alphabetical ordered list of students tend to do better than the rest of the class. Possible explanation might be use of alphabetical sorting during examinations, which creates uneven incentives among students. To support this explanation a model of student's decision under risk is presented and discussed.